COPD exacerbation and diaphragmatic dysfunction: Conditions with mutual influence influencing outcomes? – Reply. Issue 4 (8th March 2017) - Marchioni, Alessandro; Tonelli, Roberto; Antenora, Federico; Fantini, Riccardo; Clini, Enrico M.
Abstract : SeeLetter